2021
DOI: 10.3389/fimmu.2021.658263
|View full text |Cite
|
Sign up to set email alerts
|

The Key Role of NAD+ in Anti-Tumor Immune Response: An Update

Abstract: Nicotinamide adenine dinucleotide (NAD+) is an important molecule that functions as a co-enzyme in numerous metabolic processes. Generated both through de novo synthesis and via salvage pathways, NAD+ is the substrate for a variety of NAD+-consuming enzymes. Among them is CD38, a cell surface ecto-enzyme widely expressed on different types of cells and endowed with the function of cADP-ribose synthases/NAD+ glycohydrolase. Surface CD38 expression is increased in different hematological and solid tumors, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 37 publications
(64 reference statements)
1
9
0
Order By: Relevance
“…We identified a role of cADPR to promote cell progression by inducing cytoplasmic calcium flux via TRPM2 channel. Consistent with our study, F. Morandi concluded that inactivation of the CD38-cADPR axis might serve as a novel therapeutic intervention in lung cancer and a recent report indicated that TRPM2 was linked with poor prognosis in patients with pancreatic ductal adenocarcinoma [ 34 , 35 ]. In addition, to understand if the promotion of cADPR on tumor proliferation, and migration was a generalized phenomenon, we also demonstrated that cADPR could promote cell proliferation and migration in variety of human cell lines which existed the expression of TRPM2.…”
Section: Discussionsupporting
confidence: 90%
“…We identified a role of cADPR to promote cell progression by inducing cytoplasmic calcium flux via TRPM2 channel. Consistent with our study, F. Morandi concluded that inactivation of the CD38-cADPR axis might serve as a novel therapeutic intervention in lung cancer and a recent report indicated that TRPM2 was linked with poor prognosis in patients with pancreatic ductal adenocarcinoma [ 34 , 35 ]. In addition, to understand if the promotion of cADPR on tumor proliferation, and migration was a generalized phenomenon, we also demonstrated that cADPR could promote cell proliferation and migration in variety of human cell lines which existed the expression of TRPM2.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, it is worth noting that the decrease of NAD + levels in CD8 + TILs is not solely regulated by CD38, which deficiency may compensate for upregulating the expression of other NADase. Notably, intracellular NAD + levels are highly coordinated by the consumption processes and biosynthesis, such as de novo synthesis and salvage pathways ( Morandi et al., 2021 ). Recently, Wang et al.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a potential therapeutic opportunity to increase the macrophage inflammatory phenotype may be to switch TAMs back to an M1 phenotype (45,46), highlighting the importance of understanding the mechanisms regulating macrophagemediated inflammation. Additionally, it is important to understand the role of different NAD + precursors in boosting T cell responses, as an alternative way to promote antitumor responses (47). In support of this hypothesis, it was recently shown that the CD38-NAD + -Sirt1 axis regulates immunotherapeutic anti-tumor T cell responses (48).…”
Section: Discussionmentioning
confidence: 99%